2018
DOI: 10.7555/jbr.32.20170096
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum lipids and severity of epithelial ovarian cancer: an observational cohort study of 349 Chinese patients

Abstract: While obesity and fat intake have been associated with the risk and prognosis of epithelial ovarian cancer, the association between the lipid levels and epithelial ovarian cancer phenotype remains controversial. We conducted a retrospective study of 349 epithelial ovarian cancer patients who received treatment at Jiangsu Cancer Hospital, China between 2011 and 2017. We analyzed age at diagnosis, blood pressure, plasma glucose content, body mass index (BMI), lipid levels and clinical parameters. Severity of epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…The mixed study conducted by Zhang et al [12] found an association between high HDL and lower OC risk, in agreement with the finding of an association between HDL and malignant OC by Onwuka JU [11]. Low HDL levels were also shown to correlate with the high severity of EOC [10], while high HDL levels showed a significant association with better progression-free survival (PFS) of EOC patients [23]. The HDL-associated serum paraoxonase activity and arylesterase activity were also significantly lower in patients with EOC than in controls [24].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The mixed study conducted by Zhang et al [12] found an association between high HDL and lower OC risk, in agreement with the finding of an association between HDL and malignant OC by Onwuka JU [11]. Low HDL levels were also shown to correlate with the high severity of EOC [10], while high HDL levels showed a significant association with better progression-free survival (PFS) of EOC patients [23]. The HDL-associated serum paraoxonase activity and arylesterase activity were also significantly lower in patients with EOC than in controls [24].…”
Section: Discussionsupporting
confidence: 75%
“…However, a retrospective study that included 267 cases showed an independent association between increased preoperative LDL levels and improved 5-year recurrencefree survival [31]. Several studies have demonstrated that LDL, APOA1, and APOB showed no significant association with OC [10][11][12]14,23,32]. In the present study, no causal role was found for LDL, APOA1, or APOB regarding the subtypes of EOC.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Finally, cis-eQTL analysis identi ed known and novel genomic variants correlated with the expression of mRNAs and miRNAs, which are associated with lipid-related phenotypes. High HDL and triglyceride levels have been correlated with increased cancer stage at diagnosis in OC patients 48 . In addition, advanced-stage OC patients with high LDL levels have a shorter PFS than patients with normal levels 49 .…”
Section: Discussionmentioning
confidence: 99%